2013
DOI: 10.1017/s0007114512005090
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-dried jaboticaba peel powder improves insulin sensitivity in high-fat-fed mice

Abstract: The peel of the native Brazilian fruit jaboticaba is rich in anthocyanins, which are known for their anti-obesity effects in animal models. The aim of the present study was to evaluate the effects of freeze-dried jaboticaba peel powder (FDJPP) on a number of metabolic parameters in a model of diet-induced obesity. Mice (n 8 per group) were initially fed on a high-fat diet (HFD, 35 % w/w) for 4 weeks and then switched to a HFD supplemented with FDJPP (1, 2 or 4 % w/w) for an additional 6 weeks. Energy intake, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 40 publications
3
47
0
6
Order By: Relevance
“…Thus, the enzymatic inhibition can be a mechanism in the obesity regulation. In recent study, Dragano, Marques, Cintra, et al (2013) reported that despite the consumption of FJP added to the high-fat did not effected on mice weight gain, insulin resistance and modulated proteins associated with obesity, inflammation and diabetes were improved.…”
Section: Weight Gain and Intake Parametersmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, the enzymatic inhibition can be a mechanism in the obesity regulation. In recent study, Dragano, Marques, Cintra, et al (2013) reported that despite the consumption of FJP added to the high-fat did not effected on mice weight gain, insulin resistance and modulated proteins associated with obesity, inflammation and diabetes were improved.…”
Section: Weight Gain and Intake Parametersmentioning
confidence: 98%
“…However, the consumption of freeze-dried foods as a source of anthocyanins added to high-fat diet has not shown effects on weight gain neither in body fat in animal models (Batista, Lenquiste, Cazarin, et al, 2014;DeFuria, Bennett, Strissel, et al, 2009;Dragano, Marques, Cintra, et al, 2013;Lenquiste, Batista, Marineli, et al, 2012;Prior, Wilkes, Rogers, Khanal, Wu, & Howard, 2010). The effects of phenolic compounds on obesity have been studied and its effect on weight gain and body mass are still divergent.…”
Section: Weight Gain and Intake Parametersmentioning
confidence: 99%
“…Among these compounds, anthocyanins have been considered particularly promising for the prevention of NAFLD (Valenti et al, 2013). The ability of anthocyanins to reduce the risk of chronic diseases has been linked to their antioxidant capacity; however, recent findings have suggested that anthocyanins may exert their beneficial effects by interacting with a wide range of molecular targets of intracellular signaling machinery (Dragano et al, 2013;Fernandes, Faria, Calhau, de Freitas, & Mateus, 2014) including key transcription factors that coordinate lipid metabolism, such as PPAR-α (Jia et al, 2013) and SREBP-1c (Hwang et al, 2011). Although there are many reports about the health benefits of anthocyanin-rich extracts, studies to test whether physiologically relevant doses of anthocyanins could exert such effects are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The fibers from FJP (Table 1) could also be responsible to enhance hypoglycemic effect, acting in synergy with polyphenols from the peel (Kim et al, 2010). In addition, studies have shown that the intake of jaboticaba peel is related to an increased insulin sensitivity in liver and adipose tissue (Dragano et al, 2013;Lenquiste et al, 2012). Studies with polyphenol and fiber-rich meals corroborate this result: reduction in plasma glucose levels by 13.04% (Esteves et al, 2011).…”
Section: Nsmentioning
confidence: 89%
“…In view of the increase in total cholesterol and LDL-cholesterol fractions in G2 and G3 groups, we may suppose that 2% FJP should represent an upper limit for dietary intake. Thus, even that other studies showed good results with the same doses (Dragano et al, 2013;Lenquiste et al, 2012), more investigations are necessary in order to elucidate the mechanisms that may cause undesirable effects.…”
Section: Nsmentioning
confidence: 98%